2013
DOI: 10.1097/bot.0b013e318283f675
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Anterior Cortical Bone Removal and Intermeniscal Ligament Damage at the Tibial Nail Entry Zone Using Parapatellar and Retropatellar Approaches

Abstract: A substantial amount of anterior bone is removed during nail entry portal creation using both parapatellar and retropatellar techniques. Intra-articular structure damage, most commonly IM ligament disruption, was also found to occur at a lower rate with retropatellar technique. Avoidance of both anterior bone removal and IM ligament damage may not be possible because of size and geometrical constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…(26) anterior cortical defects are present with her the IM nail was placed in a infrapatellar or a suprapatellar technique. (27) Our study identified smoking as a predictor of knee pain. Ryan et al showed an inverse relationship between smoking and union 11 .…”
Section: Discussionmentioning
confidence: 77%
“…(26) anterior cortical defects are present with her the IM nail was placed in a infrapatellar or a suprapatellar technique. (27) Our study identified smoking as a predictor of knee pain. Ryan et al showed an inverse relationship between smoking and union 11 .…”
Section: Discussionmentioning
confidence: 77%
“…After the introduction of the retro-patellar approach for tibial nailing, its safety was questioned and cadaveric studies were conducted. 8 , 20 In their study on adult cadavers, Bible et al 8 reported that the retro-patellar technique was a safe alternative with no meniscal or cruciate ligament injury – as in the parapatellar approach – and less inter-meniscal ligament injury. In their cadaveric study, Eastman et al 20 reported that the injury risks to the inter-meniscal ligament and the medial meniscus, which are comparable with the classical approach, could be prevented by avoiding excessive medial entry.…”
Section: Discussionmentioning
confidence: 99%
“…The cannula used for suprapatellar nailing limits posterior translation of the starting guidewire at the level of the trochlea because the guidewire is centered within the cannula. This leads either to the guidewire entry site being forced anteriorly, which may lead to anterior translation of the starting point and increased reaming of the anterior tibial cortex, 18 or to the trajectory being forced posteriorly, which may lead to the nail displacing the fracture. (Figure 4) A simple solution to address this issue is to flex the knee more as this better exposes the starting point.…”
Section: Pearl 1: Semi-extended Positioningmentioning
confidence: 99%